Efeitos da Atorvastatina (Citalor®) sobre as sequelas neurohistológicas e comportamentais induzidas por hipoperfusão cerebral crônica em ratos de meia-idade - Zaghi, Gislene Gonçalves Dias (2015)
Chronic cerebral hypoperfusion (CCH) may be involved in the pathophysiology of neurodegenerative diseases associated with aging, such as Alzheimer's disease and dementia of vascular origin. Prevention or treatment of some risk factors (e.g., chronic hypertension, atherosclerosis, chronic heart diseases, etc.) is the primary recommendation to reduce the prevalence of neurodegenerative diseases associated with chronic cerebrovascular insuficiency. However, once a condition of CCH has been installed, one issue is whether the progression of neuropathological and functional sequelae can be attenuated by some pharmacological treatment. Statins are inhibitors of the enzyme HMG-CoA reductase, the rate-limiting step for the biosynthesis of cholesterol. Apart from their cholesterol-lowering effects, statins exert pleitropic effects including improvement in endothelial function, reduction of oxidative stress and inflammation, suppression of apoptosis in endothelial cells, and stimulation of angiogenesis. This statin-mediated pleiotropism has been suggested to underly the effects of statins in reducing both infarct size and neurological deficits in animal models of stroke. However, whether statins can be beneficial under conditions of CCH has not been investigated. To invstigate whether the treatment with atorvastatin (Citalor®) attenuates the neurodegeneration and memory deficit caused by CCH in middle-aged rats. Intact, middle-aged rats (12-15 months of age) were trained for 15 days to learn a radial maze task, then subjected to 3-stage, 4-vessel occlusion/internal carotid artery (4-VO/ICA) model of chronic cerebral hypoperfusion. Atorvastatin (10 mg/kg, p.o.) was administered for 42 days or 15 days, beginning approximately 5 hours after the first occlusion stage. The performance of retrograde memory was measured 7, 14, 21, 28 and 35 days of 4-VO/ICA. At the end of behavioral tests, the brain was examined for hippocampal and cortical neurodegeneration. Chronic cerebral hypoperfusion caused persistent retrograde amnesia, which was reversed by atorvastatin after both long-term and short-term treatment. This antiamnesic effect of atorvastatin was sustained throughout the experiment, even after discontinuing treatment (15-day treatment group). This effect occurred in the absence of histological neuroprotection. The present data suggest that atorvastatin (and perhaps other statins) represent a potential strategy for the treatment of cognitive sequelae associated with CCH.